Drug Related Problem pada Pasien Spinal Cord Injury di Bagian Rehabilitasi Medik Rumah Sakit Umum Pusat Fatmawati Jakarta Periode Januari - Juli 2019 - Triana Yudhorini, Linda (RSUP Fatmawati, 2022)
The excellent service paradigm for patients (patient oriented) for Clinical Pharmacists in Hospitals is a responsibility to improve the quality of patient drug therapy, including preventing drug-related problems (DRP). Research Methods: The method used in this study is a descriptive analytical method and data has taken with retrospective study. Drug therapy assessment especially the drug related problem has found in large rounds (visites) of Spinal Cord Injury patients in the Medical Rehabilitation Section of Fatmawati Hospital, Jakarta. Large rounds / visites are carried out by a clinical team consisting of Doctors, Clinical Pharmacist, Nurses, Psychologists, Nutritionists, Physiotherapists, Occupational Therapists, Orthhetic Prosthetics and Social Medical Officers. Research Results: After 28 rounds / visits were carried out from January to July 2019 with a total of 267 patients, it was found that 82% of patients had drug related problems. The types of DRP that occur regarding drug interactions are 73%, treatment time is 24%, and side effects are 3%. Conclusion: The drug related problems (DRP) that were found in the round / visit activities from January to July 2019 were 82% and those that were not found by DRP were 18%. Keywords: Drug Related Problems, Spinal Cord Injury, Visits, Large Round